Teaching Reproducible Methods in Economics at Liberal Arts Colleges: A Survey - Anthony Underwood; Aidan Sichel; Emily C. Marshall (Journal of Statistics and Data Science Education, 2024)
Economics has become increasingly empirical and, alongside this shift, has come more demand for improved transparency and reproducibility in empirical economic research. In this article, we distribute a survey to almost 1500 economics faculty from the top 161 liberal arts colleges with an economics major (according to U.S. News & World Report) in the United States to determine the prevalence of teaching reproducible methods in undergraduate economics, summarize the most-common methods of instruction, and determine the intended student learning objectives. We find that of the economics faculty at liberal arts colleges who teach these reproducible methods, most do so in advanced upper-level (42%) and basic econometrics (31%) courses. Those faculty report teaching reproducibility using the following methods: transparent coding (85%), organizational skills (78%), and producing replication documentation (47%) through individual research projects (82%), homework assignments (55%), and/or workshops (33%). We conclude with some qualitative text analysis to shed light on the intended learning objectives and find that research skills (59%) and the importance of reproducibility (37%) are the most common reasons cited for teaching these methods.